Trends in induction of labour and associated co-morbidities and demographics in Queensland, Australia from 2001 to 2020: a population-based study - Nigel Lee; Emma Ballard; Tracy Humphrey (BMC Pregnancy and Childbirth)
Abstract Background Amongst women who plan a vaginal birth at term, previous studies have reported that rates of induction of labour are increasing potentially impacting other labour and birth outcomes. Indications for induction of labour (IOL) have changed over time though the influences of parity and demographic factors such as age, ethnicity and regionality are not often considered. The aim of this study was to describe the changes in demographic, co-morbidity, IOL indication and clinical outcomes in women undertaking a planned cephalic vaginal birth at term over a 20 year period. Methods A retrospective population-based study was undertaken using routinely collected anonymised perinatal data from Queensland, Australia from January 2001 to December 2020. We included all singleton term (≥ 37 weeks) planned vaginal births. A total of 836,065 births met the study criteria. Data for pregnancy complications and IOL indications were grouped by ICD-10 codes. Analysis was stratified by parity and presented as frequency and percentages over time and the difference in percentages between two defined years. Results Rates of IOL increased by 15.5% (31.6 to 47.1%) in nulliparous and 14.6% (26.2 to 40.8% in multiparous women, most notable from 2015 onwards. Over the same period infants born between 37 and 38 weeks gestation increased by 13.9%. (18.1–32%). Amongst co-morbidities gestational diabetes increased from 3.8 to 12.8% and anaemia from 1.7 to 8.1%. As an indication for IOL prolonged pregnancy decreased from 41.0 to 11.2%. In nulliparous women the percentage of intact perineum decreased from 21.3 to 6.7% while episiotomy increased from 20.2 to 38.8%. Conclusions We conclude that for women planning a vaginal birth not only has the rate of IOL increased substantially over the last two decades there also appears to be considerable interaction between demographic, co-morbidity, IOL indications and clinical outcomes that warrants further large population-based research.